Mechatronic system for the control of fertilizer and pesticide granules dispensers of a fertilizer seeder - Torres Sandoval, Julio; Romantchik Kriuchkova, Eugenio; López Cruz, Irineo L.; López Canteñs, Gilberto De J. (Revista Mexicana de Ciencias Agrícolas, 2018)
The variable dosing machines make use of mechatronic systems for the drive and control of the dosers, replacing the traditional mechanical systems constituted by a drive wheel, transmission by chains and gears. Mechatronic systems allow a continuous and real-time change of the application dose. In this work a mechatronic system was developed for the control of fertilizer and granulated pesticide dispensers, which was adapted to a fertilizer seeder. The system is based on microcontrollers as a processing and control unit, as well as direct current motors with encoders to drive the dispensers. Changes in the application dose are achieved by controlling the rotation frequency of the dosing devices, using the pulse width modulation technique and the proportional-integral-derivative or proportional-integral control. The performance of the mechatronic system, to control the frequency of rotation of the fertilizer doser allows a lifting time of less than one second, maximum overshoot 14% and settling time of 1.5 to 2 s at frequencies ranging from 5 to 35 rev/min. In the case of the pesticide dispenser, the lifting time is less than one second, on maximum elongation less than 10% and settling time of 1.5 s for frequencies above 100 rev/min, at frequencies below this value variations of The control signal exceeds ±5%. Overall, the performance of the SM meets the requirements of variable dosing machines.
Keywords: microcontroller; PWM; PID control; fertilizer and agrochemical dosers